Circular economy in supply chain management : a framework for database tool development to enhance sustainability - Mayanti, Bening; Helo, Petri (Taylor & Francis, 2024)
The study surveys circular economy (CE) theoretical building blocks, conceptualisation, and practical implementation within the supply chain. A narrative review synthesises the knowledge and maps research in the CE field. There are six major building blocks: waste management, industrial ecology, bioeconomy, cradle to cradle, green supply chain management, and product-service system. The paper examines their role and their overlapping activity within the supply chain. This study also generates a database containing 43 circular strategies, based on different stages in the supply chain. Each strategy is marked by its contribution towards CE, such as resource conservation, narrowing the loop, slowing the loop, or closing the loop. The database can assist actors to implement possible circular actions and policy makers to formulate supportive legislation. This study contributes to the contention of CE and its implementation.
Keywords: Circularity; sustainability; reduce; repair; reuse; recycle; fi=Tuotantotalous|en=Industrial Management|